Analysis of Conventional and Novel Delay Lines: A Numerical Study - Ramahi, Omar M. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
Delay lines are convenient circuit elements used to introduce delay between circuit board components to achieve required timing. Serpentine or meander lines are the most common of delay lines. These lines introduce delay but also introduce spurious dispersion that makes the signal appear as if it is arriving earlier than expected. The cause of such spurious speed-up or skew is analyzed qualitatively. Previous work found that owing to the periodicity inherent in the serpentine line structure, the crosstalk noise accumulates synchronously, thus creating a higher potential for triggering false logic. Numerical simulations are performed using the Finite-Difference Time-Domain (FDTD) method to corroborate the qualitative prediction with physical behavior. Based on the understanding of the coupling mechanism in periodic serpentine lines, a qualitative prediction can be made of the behavior of novel delay lines such as the spiral line. A new delay line, the concentric Cs delay lines, is introduced. The design of the new line is based on forcing the crosstalk noise to spread over time, or to accumulate asynchronously, thus enhancing the integrity of the received signal.